Blogging Wounded Manhood: Negotiating Hegemonic Masculinity and the Crisis of the Male (In)fertile Body. Issue 1 (2nd January 2021) - Rome, Jennifer Marie
Abstract: Male (in)fertility blogs intervene into vernacular and public conceptions of both infertility and manliness. (In)fertility is a destabilizing condition that leads some men to feel marginalized by their experience. This article illustrates how discourses of male (in)fertility are caught up in a struggle of hegemonic masculinity as defined by the wounded male body and the affordances of network media. Examining a series of men's infertility blogs, I argue that men put forth their wounds and scars in ways that both challenge and recuperate hegemonic masculinity. Though it is important for men to share common experiences, the rhetorical uptake of male (in)fertility through the language of crisis and victimization serves to reaffirm cis, white, hetero masculinity's hegemony. Such discourses embrace men's wounds to fortify a position of solidarity through the adversity of (in)fertility.